2008
DOI: 10.1037/0096-1523.34.4.919
|View full text |Cite
|
Sign up to set email alerts
|

Tuning in to another person's action capabilities: Perceiving maximal jumping-reach height from walking kinematics.

Abstract: Three experiments investigated the ability to perceive the maximum height to which another actor could jump to reach an object. Experiment 1 determined the accuracy of estimates for another actor's maximal reach-with-jump height and compared these estimates to estimates of the actor's standing maximal reaching height and to estimates of the perceiver's own maximal reaching and reach-with-jump height. Perception of another actor's maximum reach-with-jump height was less accurate than the other estimates, but st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
80
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 31 publications
(37 reference statements)
2
80
1
Order By: Relevance
“…Ramenzoni et al (2008) found that after watching an actor walk while the actor wore ankle weights that reduced his or her maximum jumping-reach height, observers who were not explicitly aware of the presence of the weights provided appropriately lower perceptual category boundaries (i.e., the boundary separating what could be reached by a vertical jump and what was out of reach) than they provided for the actor when he or she was unencumbered. The result indicates that observers are often quite sensitive to the action capabilities of others or at least to changes in action capabilities.…”
Section: Do Perceived Affordances Formentioning
confidence: 99%
See 4 more Smart Citations
“…Ramenzoni et al (2008) found that after watching an actor walk while the actor wore ankle weights that reduced his or her maximum jumping-reach height, observers who were not explicitly aware of the presence of the weights provided appropriately lower perceptual category boundaries (i.e., the boundary separating what could be reached by a vertical jump and what was out of reach) than they provided for the actor when he or she was unencumbered. The result indicates that observers are often quite sensitive to the action capabilities of others or at least to changes in action capabilities.…”
Section: Do Perceived Affordances Formentioning
confidence: 99%
“…In previous studies, we found that although perceivers are fairly accurate at perceiving maximum jumping-reach height affordances for themselves and an actor, some degree of error-typically, underestimation on the order of 10-15 cm (e.g., Ramenzoni et al, 2008)-was observed. This indicates room for improvement that could be achieved through learning.…”
Section: The Present Studymentioning
confidence: 99%
See 3 more Smart Citations